Synergistic role of electron-trapped oxygen vacancy and exposed TiO2 [001] facets toward electrochemical p-nitrophenol reduction: Characterization, performance and mechanism - Ni, Congcong; Li, Yifan; Meng, Xianzhe; Liu, Shuliang; Luo, Siyi; Guan, Jing; Jiang, Bo (Chemical engineering journal (Lausanne, Switzerland : 1996), 2021)
[Display omitted] •Electron-trapped oxygen vacancy was introduced in Ti/TiO2-001 by H2 reduction.•Increasing electron-trapped oxygen vacancy in Ti/TiO2-001 enhanced its reduction activity.•The synergistic role between electron-trapped oxygen vacancy and [001] facets was proposed.•Electron-trapped oxygen vacancy on TiO2 acted as adsorption site and reactivity sites. Despite the fact that electron-trapped oxygen vacancy and [001] facets fundamentally affect the reactivity of TiO2, their synergistic role in the electrochemical activity of TiO2 toward p-nitrophenol (p-NP) reduction is still unknown. In this study, defective and [001] facets engineered TiO2 cathode, i.e. Ti/TiO2−x-001, was prepared for p-NP reduction. In comparison to defective Ti/TiO2 cathode with [101] facets (Ti/TiO2−x-101), the combination of the electron-trapped oxygen vacancy and [001] facets exhibited a synergistic effect to improve the electrochemical reduction efficiency of TiO2. Density functional theory calculations verified that the introduction of [001] facets and electron-trapped oxygen vacancy on TiO2 was beneficial to facilitate electron transfer and improve the indirect reduction efficiency for p-NP electrochemical reduction. Moreover, the electron-trapped oxygen vacancy extent of Ti/TiO2−x-001 was modulated by adjusting reduction temperature (250–650 °C). The maximum electron-trapped oxygen vacancy amount of Ti/TiO2−x-001 was attained at the reduction temperature of 350 °C, which resulted in the highest p-NP reduction efficiency of 99.3%, accompanying the p-AP selectivity of 89.5%. In this case, the abundant active and adsorption sites were provided on the surface of Ti/TiO2−x-001 prepared at 350 °C, in which p-NP adsorption coefficient and electrochemical surface area increased to 1.01 L mg−1 and 25 cm2, respectively. Generally, this work provides a paradigm for the design of efficient non-metallic catalyst for nitroaromatic chemicals reduction.